"In the Name of Humanity": Nazi Doctors and Human Experiments in German Concentration Camps. (17th November 2020) - de Leeuw, Daan
Abstract: During the Second World War over two hundred and fifty German doctors conducted medical experiments on human beings. Jurists and scholars have pondered ever since how doctors educated to heal could harm and even kill. Robert Jay Lifton has argued that psychological "doubling" could explain their crimes: their Faustian bargain with Nazism outweighed their Hippocratic Oath. Here the author argues, however, that Lifton's theory does not apply to these Nazi doctors because there is no indication that they recognized ethical constraints against human experimentation. To explain how "healers became killers, " the author focuses on the broader historical aspects of their behavior.